The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/s002130050365
|View full text |Cite
|
Sign up to set email alerts
|

Differences in extracellular dopamine concentrations in the nucleus accumbens during response-dependent and response-independent cocaine administration in the rat

Abstract: Studies indicate that nucleus accumbens (NAcc) dopamine neurotransmission is involved in the reinforcing and direct effects of cocaine. The present study was initiated to explore further the relationship of NAcc extracellular dopamine concentrations ([DA]e) and cocaine self-administration using a yoked littermate design. In the first experiment, one rat from each litter was trained to self-administer cocaine i.v. (SA: 0.33 mg/inf) under a fixed ratio 2 schedule, while a second rat received simultaneous infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
217
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(239 citation statements)
references
References 49 publications
(54 reference statements)
20
217
2
Order By: Relevance
“…This relatively rapid time course is consistent with evidence that estradiol has non-genomic effects that may precede its traditional genomic steroid actions and influence behavior as well as neuroendocrine and reproductive function (Falkenstein et al, 2000;Moore and Evans, 1999;Vasudevan and Pfaff, 2007;Wong et al, 1996). Both estradiol and cocaine increase extracellular dopamine levels measured in microdialysis studies in rodents (Becker, 1999;Becker et al, 2001;Di Chiara, 1995;Hemby et al, 1997), and dopamine is generally thought to subserve the reinforcing effects of cocaine (Kuhar et al, 1991;Woolverton and Johnson, 1992). The extent to which cocaine-induced increases in estradiol levels may contribute to cocaine-related increases in extracellular dopamine in the nucleus accumbens and ventral striatum is unknown.…”
Section: Introductionsupporting
confidence: 71%
“…This relatively rapid time course is consistent with evidence that estradiol has non-genomic effects that may precede its traditional genomic steroid actions and influence behavior as well as neuroendocrine and reproductive function (Falkenstein et al, 2000;Moore and Evans, 1999;Vasudevan and Pfaff, 2007;Wong et al, 1996). Both estradiol and cocaine increase extracellular dopamine levels measured in microdialysis studies in rodents (Becker, 1999;Becker et al, 2001;Di Chiara, 1995;Hemby et al, 1997), and dopamine is generally thought to subserve the reinforcing effects of cocaine (Kuhar et al, 1991;Woolverton and Johnson, 1992). The extent to which cocaine-induced increases in estradiol levels may contribute to cocaine-related increases in extracellular dopamine in the nucleus accumbens and ventral striatum is unknown.…”
Section: Introductionsupporting
confidence: 71%
“…Finally, there is evidence that the contingencies governing drug administration can even affect neurochemical measures. In this regard, Hemby et al (1997) demonstrated significantly higher extracellular dopamine concentrations in the nucleus accumbens, despite equivalent brain concentrations of drug, in rats self-administering cocaine, as compared to a yoked control group. Furthermore, Stefanski et al (1999) observed region-specific downregulations of D 1 and D 2 receptors in rat brain after a 5-week regimen of methamphetamine self-administration but not after equivalent response-independent drug exposure using a yoked control design.…”
Section: Reinforcing Effects Of Mdma and Its Analogsmentioning
confidence: 87%
“…[6][7][8] These data support numerous studies in animal models demonstrating the role of the NAc in the reinforcing effects of cocaine. [9][10][11][12][13][14] Although regional and neurotransmitter-centric hypotheses have provided a framework for studying the acute and chronic effects of cocaine intake on the brain, detailed mechanisms of intracellular neuroadaptations have only recently become known. Repeated cocaine use induces biochemical adaptations in reinforcement-relevant brain regions [15][16][17] and these adaptations appear to be relevant to the processes of sensitization, craving, withdrawal and relapse.…”
Section: Introductionmentioning
confidence: 99%